Mentoring – Performance Management Tool - Vodák, Josef (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
In this article author discusses achieving success of a company through Performance Management, especially with focus on human capital. From a wide variety of performance management tools article focuses on mentoring as a valuable method which is less known than coaching. This article discussed reasons for using mentoring in a company, benefits for mentee, company and mentors. In addition, it shows what aspects play a key role in good implementation of this method and compares mentoring and coaching.

W artykule przedstawiono możliwości osiągnięcia sukcesu przez organizację dzięki Zarządzaniu działalnością, ze szczególnym uwzględnieniem kapitału ludzkiego. Spośród wielu różnorodnych narzędzi zarządzania działalnością w opracowaniu zaprezentowano mentoring jako wartościową metodę, która jest mniej znana od coachingu. W artykule dyskusji poddano przyczyny wykorzystania mentoringu w firmie, korzyści dla podopiecznego, firmy i mentora. Ponadto zwrócono uwagę na kluczowe czynniki właściwej implementacji tej metody oraz dokonano porównania mentoringu i coachingu.